Anti-fouling performance of chevron plate heat exchanger by the surface modification. (December 2019) - Ahn, Ho Seon; Kim, Koung Moon; Lim, Sun Taek; Lee, Chang Hun; Han, Seok Won; Choi, Hong; Koo, Sangmo; Kim, Namkeun; Jerng, Dong-Wook; Wongwises, Somchai
Highlights: The stainless steel modified surface was fabricated for chevron plate heat exchanger. The anti-fouling performance would be estimated on bare, modified, PMMA and BN coated. The dynamic wetting characteristics could be possible to explain the anti-fouling performance. Abstract: In this study, we aimed to develop a method for modifying SUS304 with micro/nanoscale holes using an electrical etching technique, and evaluated its impact on the anti-fouling performance of chevron plate heat exchangers. The modified SUS304 specimen exhibited hydrophobic wetting characteristics; however, water droplets stuck to the wall under inclined orientations at angles of 30° and 60°. We coated the modified SUS304 specimen with polymer (polymethyl methacrylate; PMMA) and hexagonal boron nitride (BN) particles to realize the hydrophobic and superhydrophobic wetting characteristics. To evaluate the anti-fouling performance of the heat exchanger, we carried out fouling acceleration experiments in a 2000 ppm CaCO3 solution for 2 h. The anti-fouling performance was determined by measuring the overall heat transfer coefficients during fouling acceleration experiments. As the operation time increased, the CaCO3 particles were deposited on the surface of the heat exchanger, the overall heat transfer coefficient decreased, and the fouling factor ultimately increased. Out of bare, modified, PMMA- and BN-coated heat exchangers, the PMMA-coated heat exchanger exhibited the strongest anti-fouling performance, with the lowest increment in the fouling factor. Based on analysis of the contact angle hysteresis (CAH) in each case, we suggest that CaCO3 particles in solution would be deposited better in the case of the highest CAH. This is possible in cases without the triple contact line, and is caused by filling the polymer into micro/nano holes on the modified surface.